Role of aluminium and magnesium effects on initiation and promotion in the renal osteodystrophy of the patients with chronic renal failure - SATO, NAOYUKI; MARUMO, FUMIAKI; TSUKAMOTO, YUSUKE; IWANAMI, SHIGERU; NAKAMRUA, MIZUHO (Nihon Jinzo Gakkai shi, 1986)
Ca, Al and Mg contents in the bone of 55 persons was measured by non-destructive neutron activation analysis. The Ca content in the bone of non-dialyzed and dialyzed patinets was found to decrease. Al and Mg were relatively higher than Ca in the patients compared to the control. The present study suggests that fluctuation in the content of Al and Mg may have some relation to renal osteodystrophy such as osteomalacia as well as similar and related disorders. Serum concentration of Al in patients receiving A1-containing phosphate binder was correlated with their creatinine clearance. However, the contamination of tap water with Al was considered more important risk factor for the Al bone disease.